Comparison and Performance Analysis of Various FACTS Devices in Power System (International Journal of Engineering and Computer Science, 2016)
In recent years, power demand has increased substantially while the expansion of power generation and transmission has been severely limited due to limited resources and environmental restrictions. This paper investigates the enhancement in voltage stability margin as well as the improvement in power transfer capability of transmission line in a power system with the incorporation of Static Synchronous Compensator (STATCOM), Fixed Capacitor Thyristor Controlled Reactor (FC-TCR and) Static Synchronous Series Compensator (SSSC). A simple transmission line system is modelled in MATLAB/SIMULINK environment. The load flow results are first obtained for an uncompensated system, and the voltage and power profiles are studied. The results so obtained are compared with the results obtained after compensating the system using STATCOM, FC-TCR and SSSC to show the voltage stability margin enhancement. The results obtained after simulation demonstrate the performance of the system for each of the FACTS devices in improving the power profile and thereby voltage stability of the same.